2018
DOI: 10.3892/mmr.2018.8681
|View full text |Cite
|
Sign up to set email alerts
|

SOX6 is downregulated in osteosarcoma and suppresses the migration, invasion and epithelial-mesenchymal transition via TWIST1 regulation

Abstract: Transcription factor SOX6 (SOX6) has been reported to serve essential roles in numerous types of cancers. However, the expression and functions of SOX6 in osteosarcoma (OS) have not been analyzed. In the present study, the patterns of SOX6 expression in OS cell lines and tissues were investigated by reverse transcription‑quantitative polymerase chain reaction and western blotting. The results of the present study revealed that SOX6 was notably downregulated in OS tissues and cell lines. Subsequently, gain‑ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…In pancreatic cancer, Sox6 was downregulated in patients with metastatic disease, and its overexpression could suppress tumor invasiveness by inhibiting EMT 22 . Similar findings were also observed in osteosarcoma 24 . In contrast, for some types of brain tumors, 20,40 SOX6 expression was higher compared with normal tissues, and high expression of SOX6 might be a potential diagnostic marker.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In pancreatic cancer, Sox6 was downregulated in patients with metastatic disease, and its overexpression could suppress tumor invasiveness by inhibiting EMT 22 . Similar findings were also observed in osteosarcoma 24 . In contrast, for some types of brain tumors, 20,40 SOX6 expression was higher compared with normal tissues, and high expression of SOX6 might be a potential diagnostic marker.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, several studies also indicated SOX6 could suppress the migration and invasion of cancer cells. In pancreatic cancer 22 and osteosarcoma, 24 SOX6 was reported to influence EMT via the regulation of Twist1 through the recruitment of HDAC1 to the promoter of the Twist1 gene. These findings suggested that SOX6 was involved in the regulation of processes involved in cancer biology and could regulate different target genes during the development of different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOX6 is aberrantly upregulated in numerous types of cancer, including pancreatic cancer (37), prostate cancer (38), ovarian cancer (29), colorectal cancer (39) and hepatocellular carcinoma (40). SOX6 may contribute to the occurrence and development of tumorigenesis and tumor development through the regulation of various biological features, including cell proliferation, cycle, apoptosis, epithelial-mesenchymal transition and metastasis (28)(29)(30). The current study demonstrated that miR-765 directly targets SOX6 to implicate the progression of MM.…”
Section: Discussionmentioning
confidence: 59%
“…3A). SOX6 was selected for further experimental validation as SOX6 is involved in the tumorigenesis and tumor development of multiple types of human cancer (28)(29)(30). A luciferase reporter assay was performed to confirm whether miR-765 directly targets the 3'-UTR of SOX6.…”
Section: Sox6 Is a Direct Target Gene Of Mir-765 In MM Cellsmentioning
confidence: 99%